Comparing the relationship between perceived characteristics of innovation (PCI) and adoption of computer based training among trainer and trainees - Yaacob, Hashim Fauzy; Yusoff, Mohd Zarir (Elsevier Ltd., 2014)
The purpose of this study is to examine the factors associated with the adoption of innovation perceived by trainer and trainees namely “perceived characteristics of innovation (PCI)” in using CBT and also to compare this relationship among trainer and trainees.The data were collected by using a set of questionnaire.The questionnaire has been designed by adopting the instruments of Perceived Characteristic of Innovation (PCI) and Adoption Questionnaire.Then, the collected data have been analyzed by using Pearson’s Correlation, regression and Z-Fisher.The finding shows that there is positive relationship between PCI and adoption, and there is a significant different in relation on compatibility factor and the adoption level on computer based training between trainers and trainees.